1988
DOI: 10.1002/hlca.19880710724
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselektive Alkylierung von 3‐Aminobutansäure in der 2‐Stellung

Abstract: The enantiomerically pure 3-aminobutanoic acids ( R )and (S)-6 are readily available by preparative HPLC separation of the two diastereoisomers 5 obtained from addition of (S)-phenethylamine to methyl crotonate and subsequent hydrogenolysis (Scheme 2). (S)-Methyl 3-(benzoy1amino)butanoate ((S)-3) is also available by enzymatic kinetic resolution with pig-liver esterase. The N-benzoyl-and N-benzyloxycarbonyl derivatives rac-3,8, and 9 of 3-aminobutanoates are doubly deprotonated with LDA and alkylated or aminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 127 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…EI-MS: 232 ( M + ) , 188 (3), 176 (3), 158 (22), 144 (67), 88 (58), .98, CHCl,)). Spectroscopic data: identical to that of the compound described in [37], but with opposite sign of optical rotation.…”
Section: General Procedures For Peptide Couplingmentioning
confidence: 77%
See 1 more Smart Citation
“…EI-MS: 232 ( M + ) , 188 (3), 176 (3), 158 (22), 144 (67), 88 (58), .98, CHCl,)). Spectroscopic data: identical to that of the compound described in [37], but with opposite sign of optical rotation.…”
Section: General Procedures For Peptide Couplingmentioning
confidence: 77%
“…NMR: in agreement with [36]. [35] [37], BuLi (8.3 ml, 10.3 mmol) was added to a soh. of (i-Pr),NH (1.47 ml, 10.3 mmol) in THF (9.2 ml) at -78".…”
Section: General Procedures For Peptide Couplingmentioning
confidence: 95%
“…Previous work of several groups has, indeed, demonstrated that alkylation of chiral dianion derivatives proceeds with high stereoselectivity. [151][152][153][154][155][156][157][158][159][160] In general, both higher yields and better stereoselectivities are observed in the alkylation reaction of the dilithio-derivative I-2Li compared with the enolate IILi. In addition, the alkylation products show opposite diastereoselectivities; compounds derived from I are of (S)-configuration, whereas the ones derived from II are of (R)-configuration.…”
Section: -140mentioning
confidence: 89%
“…All 1 H NMR spectra were recorded in deuterochloroform, unless stated otherwise, using tetramethylsilane (TMS) as an internal standard. 13 C spectra were recorded at 75 MHz on the Varian Mercury 300 NMR spectrometer with proton decoupling at 300 MHz. All 13 C spectra were recorded in deuterochloroform, unless stated otherwise, with TMS as an internal standard.…”
Section: Chemicals and Solventsmentioning
confidence: 99%